2017
DOI: 10.1039/c7dt00283a
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) thiosemicarbazone complexes induce marked ROS accumulation and promote nrf2-mediated antioxidant response in highly resistant breast cancer cells

Abstract: A series of water-soluble sodium salts of 3-formyl-4-hydroxybenzenesulfonic acid thiosemicarbazones (or sodium 5-sulfonate-salicylaldehyde thiosemicarbazones) containing different substituents at the terminal nitrogen atom (H, Me, Et, Ph) and their copper(ii) complexes have been prepared and characterised by elemental analysis, spectroscopic techniques (IR, UV-vis, H NMR), ESI mass spectrometry, X-ray crystallography and cyclic voltammetry. The proligands and their copper(ii) complexes exhibit moderate water s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 67 publications
8
66
0
Order By: Relevance
“…20 This proposes that the cytotoxicity of Cu(SBCM) 2 could be due to the production of intracellular ROS as copper complex of other variants have found that they induced cell death by induction of high oxidative stress. [21][22][23][24][25] Unexpectedly, based on the DCFH-DA assay results (Fig. 8), Cu(SBCM) 2 did not increase the ROS production in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 82%
“…20 This proposes that the cytotoxicity of Cu(SBCM) 2 could be due to the production of intracellular ROS as copper complex of other variants have found that they induced cell death by induction of high oxidative stress. [21][22][23][24][25] Unexpectedly, based on the DCFH-DA assay results (Fig. 8), Cu(SBCM) 2 did not increase the ROS production in both MCF-7 and MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast, incubation of cells with 1 and 2 shows a significant (p < 0.0001) increase in the SOD activity. These results indicate that copper complexes can initiate Fenton reactions, intracellularly resulting in ROS accumulation [54,134]. Furthermore, the Cu I ions can react with molecular oxygen and be re-oxidised to Cu II generating reactive superoxide radicals (see Equation 4) and thereby increasing the SOD activity.…”
Section: Biological Activitymentioning
confidence: 98%
“…Furthermore, the coordination of such ligands to palladium could give rise to compounds with a mechanism of action distinct from that of 'cisplatin like' complexes, since thiosemicarbazone derivatives complexes have shown different molecular targets. 5,18,19 In this work, new palladium complexes derived from pyrene thiosemicarbazones were prepared, and designed to have sufficient stability against hydrolysis in solution together with a 'non-cisplatin like' mechanism of action against cancer cells, to overcome the acquired resistance of platinum-based drugs.…”
Section: Introductionmentioning
confidence: 99%